Dioscorides' Investigations on Pharmacological Properties of Pistacia lentiscus L. and Marrubium Vulgare L.: Two Plants with Timeless Medicinal Use - John Pouris*; Frantzeska Stylianou (Lorestan University of Medical Sciences, 2021)
Pistacia lentiscus L. and Marrubium vulgare L. are two plants described by Pedanius Dioscorides that have been examined for their use in medicine. This review aimed to determine whether the pharmacological properties of these two plants identified by Dioscorides are consistent with modern pharmacological data. There will also be a record of the chemicals identified by these plants from different studies and their contributions to disease control. A hundred literature references were studied in this review work but only 51 references were included. Many of the substances isolated from P.lentiscus and M.vulgare have pharmacological properties described by Dioscorides. The pharmacological properties of these two plants have been certified by modern techniques described in several of the articles mentioned in this mini review. Many studies have shown that mastic oil (originated from P.lentiscus) has a chemotype dominated by monoterpene hydrocarbons, alcohols, aldehydes, ethers, oxides, furans, sesquiterpene hydrocarbons and monoterpene hydrocarbons with specific biological effects. The chemical composition of the aerial parts of Marrubium vulgare consist of y-eudesmol, β - citronellol, citronellyl formate, germacrene D, ﬂavonoids and polyphenolic compounds. It can be concluded that the results are highly consistent with the observations of Dioscorides. Further studies can reveal if the rest of the plants listed in the book De Materia Medica are related to the pharmacological properties recently reported. There are many substances with pharmacological use in plants described by Dioscorides that have remained largely unnoticed to date. Many texts written so far contain a wealth of knowledge. This information combined with state-of-the-art techniques could lead to faster and more targeted results in the field of herbal medicine.